معالم التّفجّع في قصيدة الرّثاء الجاهليّة: "رثاء الأخ أنموذجاً" (Journal of Hama University, 2022)
The research strives to extrapolate the features of mourning in the poem of lamentation of the pre-Islamic brother, and stands in the way of achieving its goal on the meaning of lamentation between the linguistic connotation and the poetic purpose, and then presents a critical look at the motives of lamentation and its components, and did not neglect to talk about the reception of literature and its critics, and ends with it. Proving the most important features of mourning in the Elegy of the Brother pre-Islamic poem.The research adopted the descriptive analytical method to reach the desired result. After extrapolating the features of grief in the Elegy of the Brother pre-Islamic poem The research came to counting grief as an emotional position that expresses the poet's mourning for the grief of loss and its psychological and physical manifestations, And it explained its most important psychological and physical manifestations in the mournful poet. The research proved that it has features that paved the way for the formulation of some meanings of lamentation, and the research has endeavored to trace it, detail it, and indicate its intellectual value.
Keywords: Features; Lamentation; Elegy; brother; Poem; Pre- Islamic